1999
DOI: 10.1074/jbc.274.19.13541
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oxidative Stress in Tumor Cytotoxic Activity of Hepatocyte Growth Factor/Scatter Factor

Abstract: In this study, we show that N-acetylcysteine (NAC), a precursor of glutathione and an intracellular free radical scavenger, almost completely prevented hepatocyte growth factor (HGF)-suppressed growth of Sarcoma 180 and Meth A cells, and HGF-induced apoptosis, assessed by DNA fragmentation, and increase in caspase-3 activity, in Sarcoma 180 cells. The reduced form of glutathione also prevented HGF-suppressed growth of the cells as effective as NAC. Ascorbic acid partially prevented the effect of HGF, but other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 63 publications
3
33
0
Order By: Relevance
“…However, a proapoptotic role of HGF (Arakaki et al, 1998;Matteucci et al, 2003;Rasola et al, 2004) and b-catenin (Kim et al, 2000;van Gijn et al, 2001;Edlund et al, 2005) was also reported in several models. Here, we show that the HGFR transduction axis and the b-catenin/TCF pathway cooperate in underpinning survival signals, whose importance probably increases during carcinoma progression.…”
Section: Discussionmentioning
confidence: 98%
“…However, a proapoptotic role of HGF (Arakaki et al, 1998;Matteucci et al, 2003;Rasola et al, 2004) and b-catenin (Kim et al, 2000;van Gijn et al, 2001;Edlund et al, 2005) was also reported in several models. Here, we show that the HGFR transduction axis and the b-catenin/TCF pathway cooperate in underpinning survival signals, whose importance probably increases during carcinoma progression.…”
Section: Discussionmentioning
confidence: 98%
“…Studies with other toxic agents have implicated ROS generation and depletion of cellular antioxidants in toxicity and induced cell death (Arakaki et al, 1999;Wolfler et al, 2001;Lee et al, 2002). To provide greater insight into the mechanism of SM action in order to identify potential treatments for exposure to this agent, we have now investigated the possible contribution of ROS generation and depletion of cellular antioxidants to SM toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase substrate-mimicking peptide inhibitors have been most frequently used to block apoptosis. Radical scavengers such as N-acetylcysteine and metalloporphyrin can protect against apoptosis induced by reactive oxygen species (15)(16)(17). Isatin sulfonamide derivatives directly inhibit effector caspases such as active caspase-3 and active caspase-7 and are able to block apoptosis induced by cycloheximide or camptothecin (18).…”
Section: Ech Preferentially Binds To Pro-caspase-8 In Intactmentioning
confidence: 99%
“…Functional and structural analyses of these regulators have contributed to our understanding of the molecular basis of Fas-mediated apoptosis. However, several non-peptide small molecules that modulate apoptosis also have been reported (15)(16)(17)(18)(19)(20)(21). These molecules are useful for dissecting the apoptosis signal transduction pathway and also may be potential candidates for therapeutic use.…”
mentioning
confidence: 99%